2021
DOI: 10.1111/jipb.13145
|View full text |Cite
|
Sign up to set email alerts
|

Engineering broad‐spectrum disease‐resistant rice by editing multiple susceptibility genes

Abstract: Rice blast and bacterial blight are important diseases of rice (Oryza sativa) caused by the fungus Magnaporthe oryzae and the bacterium Xanthomonas oryzae pv. oryzae (Xoo), respectively. Breeding rice varieties for broad‐spectrum resistance is considered the most effective and sustainable approach to controlling both diseases. Although dominant resistance genes have been extensively used in rice breeding and production, generating disease‐resistant varieties by altering susceptibility (S) genes that facilitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 43 publications
(58 reference statements)
2
23
0
2
Order By: Relevance
“…More Xoo strains will be tested in these mutants to investigate their broad‐spectrum resistance to the bacterial blight. A recent study showed that CRISPR/Cas9‐mediated multiplex editing of the Pi21 , Bsr‐d1 as well as a well‐known Xoo ‐resistant gene Xa5 generated pi21‐bsr‐d1‐xa5 triple mutant which conferred resistant to both blast and bacterial blight (Tao et al ., 2021 ). In our study, on one hand, we further compared the blast resistance level among Bsr‐d1 , Pi21 and ERF922 single mutants and identified the erf922 mutant with the strongest blast resistance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More Xoo strains will be tested in these mutants to investigate their broad‐spectrum resistance to the bacterial blight. A recent study showed that CRISPR/Cas9‐mediated multiplex editing of the Pi21 , Bsr‐d1 as well as a well‐known Xoo ‐resistant gene Xa5 generated pi21‐bsr‐d1‐xa5 triple mutant which conferred resistant to both blast and bacterial blight (Tao et al ., 2021 ). In our study, on one hand, we further compared the blast resistance level among Bsr‐d1 , Pi21 and ERF922 single mutants and identified the erf922 mutant with the strongest blast resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, on one hand, we further compared the blast resistance level among Bsr‐d1 , Pi21 and ERF922 single mutants and identified the erf922 mutant with the strongest blast resistance. On the other hand, our study described the new roles of Pi21 as well as ERF922 in the resistance to Xoo , which could well explain why the pi21‐bsr‐d1‐xa5 triple mutant exhibited much stronger resistance to Xoo than xa5 single mutant in the previous study (Tao et al ., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Editing the EBEs of S genes OsSWEET11 , OsSWEET13 , and OsSWEET14 in rice varieties japonica Kitaake and indica IR64 and Ciherang-sub1 resulted in loss of induction of these S genes by Xoo and broad-spectrum resistance against Xoo [ 123 , 124 , 125 , 126 ]. Similar strategies were used in the modification of S genes, Pi21 , Bsr-d1 , and Xa5 to obtain broad-spectrum resistance rice against Xoo and M. oryzae [ 127 ]. In addition, it was well summarized that editing the open reading frame of susceptibility defense regulators could obtain broad-spectrum resistance rice plants in the Wang’s review ( Figure 2 b) [ 128 ].…”
Section: Strategies For Broad-spectrum Disease Resistance Rice Breedingmentioning
confidence: 99%